CHARACTERISTICS OF THE NEO-VICTORIAN NOVEL IN THE "FRENCH LIEUTENANT’S WOMAN" BY JOHN FOWLES - Sodikova, Bakhtigul; Berdiyev, Suhrob; Togaev, Bobur; Hafizov, Sarvar; Maxsumov, Rustam (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
In this article, literary currents (modernism, postmodernism) are considered as a reaction to the violation of human rights, the horrors of war and post-war events, the special direction of the current of postmodernism in English literature is the wide use of the term "Victorian literature", the definition and interpretation of the neo-Victorian period in postmodernism, the use of general research methods such as comparison and evaluation of the period, specific literary approaches in the literary work, such as the historical-cultural approach in the study of the relevant time and place, some main features of postmodernism, the author's point of view, the demonstration of philosophical-aesthetic dominance, and an opinion about psychological structural approaches is held.